2015
DOI: 10.3390/molecules200815392
|View full text |Cite|
|
Sign up to set email alerts
|

The Potential Use of Natural and Structural Analogues of Antimicrobial Peptides in the Fight against Neglected Tropical Diseases

Abstract: Abstract:Recently, research into the development of new antimicrobial agents has been driven by the increase in resistance to traditional antibiotics and Emerging Infectious Diseases. Antimicrobial peptides (AMPs) are promising candidates as alternatives to current antibiotics in the treatment and prevention of microbial infections. AMPs are produced by all known living species, displaying direct antimicrobial killing activity and playing an important role in innate immunity. To date, more than 2000 AMPs have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 236 publications
1
54
0
1
Order By: Relevance
“…However, lysis percentages were very low, thereby agreeing with that reported for various AMPs; SA-2-SA-5 has 10% maximum hemolysis at 500 μg/mL and magainin 1 has maximum 3% hemolysis at 50 μM. Other natural AMPs, such as melittin, have 100% hemolytic activity at 12 μg/mL (Maher and McClean, 2006; Joshi et al, 2010; Lewies et al, 2015). Such low hemolytic capability could be associated with a lower percentage of PE in RBC external monolayer (Daleke, 2008) since it was observed that peptide 35409 preferentially interacted with this phospholipid ( Figure 5B ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, lysis percentages were very low, thereby agreeing with that reported for various AMPs; SA-2-SA-5 has 10% maximum hemolysis at 500 μg/mL and magainin 1 has maximum 3% hemolysis at 50 μM. Other natural AMPs, such as melittin, have 100% hemolytic activity at 12 μg/mL (Maher and McClean, 2006; Joshi et al, 2010; Lewies et al, 2015). Such low hemolytic capability could be associated with a lower percentage of PE in RBC external monolayer (Daleke, 2008) since it was observed that peptide 35409 preferentially interacted with this phospholipid ( Figure 5B ).…”
Section: Discussionsupporting
confidence: 85%
“…Most of them share common characteristics, such as length (12-100 residues), positive net charge and amphipathic structures; however; they have little sequence homology and a broad range of secondary structures (Lewies et al, 2015). AMPs’ most important mechanism of action lies in altering membrane organization and depolarization through electrostatic and hydrophobic interactions with negatively charged lipids on cell membrane (Yeaman and Yount, 2003; Reddy et al, 2004; Teixeira et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…α-helical AMPs are linear in aqueous solution and will assume amphipathic helical structures when they interact with bacterial membranes or in the presence of organic solvents [6]. Magainin-2 and LL-37 are examples of peptides that belong to this group (Figure 2a,b) [20,21]. In the α-helix conformation, the distance between two close amino acids is around 0.15 nm while the angle between them with regard to the center is around 100 degrees from the top view [18].…”
Section: Structurementioning
confidence: 99%
“…α‐helical AMPs have a linear structure in aqueous solution and become amphipathic helical structure upon contacting bacterial membrane or organic solvents (Mahlapuu, Hakansson, Ringstad, & Bjorn, ). Most members of this class are free of cysteine residues and contain around 50% hydrophobic residues that promote the amphiphilic conformation upon contact with a membrane (Lewies, Wentzel, Jacobs, & Du Plessis, ). Furthermore, α‐helical AMPs are often broad spectrum and are capable of interacting with various types of membranes.…”
Section: Structural Classificationmentioning
confidence: 99%